The most commonly used Industry 4.0 technologies in manufacturing: a systematic literature review - Rajković, T. (Advances in production engineering and management, 2025)
Industry 4.0 presents a modern concept in production management that applies digital technologies and enables more efficient and faster production with minimal waste. This paper presents the concept of Industry 4.0, its development over the years, and related technologies for digitalization and automation of production management. A comprehensive systematic literature review based on the scholarly database Scopus was conducted, using VOSviewer software, along with additional analysis of selected articles by the authors of this paper. The main objective of the paper is to define the technologies most applied in production management and their importance and impact on production. Based on these results, the most important and commonly applied technologies in the manufacturing industry are defined: the Internet of Things (IoT), Artificial Intelligence (AI), and Big Data (BD). This paper highlights the advantages, disadvantages, and potential improvements of each technology in manufacturing companies. The intention of this article is to highlight the importance of applying technologies for digitalization and automation, as well as the concept of Industry 4.0, in manufacturing companies through the presentation of the literature review results. This paper is of high importance for manufacturing companies and managers in supporting decision-making regarding the application of technologies for digitalization, automation, and business improvement.
Keywords: artificial intelligence; big data; digitalizacija; digitalization; industry 4.0; Internet of Things; internet stvari; IoT; smart manufacturing; systematic literature review; technology adoption; umetna inteligenca; veliki podatki